ANTIOXIDANT AND ANTIMICROBIAL ACTIVITY OF CAPULIN (Prunus serotina subsp capuli) EXTRACTS - M. Jimenez (Revista Mexicana de Ingeniería Química, 2011)
Capulin (Prunus serotina subsp. capuli) is an annual fruit widely used in Mexico for the elaboration of several traditional products, such as medicinal tea, which is considered to present antioxidant and antimicrobial properties. The aim of this work was to evaluate the antioxidant and antimicrobial properties of aqueous, acetone, ethanol and methanol extracts. The ethanol extract presented a high anthocyanin (102+7.70 mg Cyd-3-glu/100 g extract) and polyphenol (1732+43.40 mg GAE /100 g extract) content and a high scavenging antioxidant activity (73.47+0.01%) in accordance with the reducing power (3.164+0.028), redox potential (395+2 mV) and optical density (0.921+0.08). It also presented antimicrobial activity against the majority of gram (-) bacteria: Salmonella typhimurium, Proteus mirabilis, Escherichia coli and Pseudomona aeruginosa, but only against one gram (+) bacterium: Staphylococcus aureus. In addition, said extract inhibited yeast activity, but had no effect on molds. Therefore, this ethanol extract could present potential as a food additive.